Management of Chylous Ascites with Octreotide in a Bangladeshi Child: A Case Report - Nurullah, Mohammed; Karim, ASM Bazlul; Rukunuzzaman, Md; Mazumder, Md Wahiduzzaman; Begum, Fahmida (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2016; VOL 40 (1) :49-51